Enhancing Career Decision Self-Efficacy through a Career Planning Intervention: A Pretest–Posttest Study among Vocational High School Students - Paisal Paisal; Tsurayya Syarif Zain; Melisa Kurnia Asfitri; Welan Mauli Angguna; Sari Bayurini Samudra; Mutiara Syafitri; Liyun Zirah; Desi Ramawati (Universitas PGRI Yogyakarta, 2026)
Abstract The rising number of young people in Indonesia who are NEET (Not in Employment, Education, or Training), especially among vocational high school graduates, indicates that the transition from education to employment remains difficult. While worldwide research indicates that career interventions might improve Career Decision Self-Efficacy (CDSE), empirical evidence in Indonesian vocational school settings is scarce, particularly concerning short-term, module-based programs. This study evaluated how well a structured career planning intervention raised the Career Decision Self-Efficacy (CDSE) of vocational high school students. A comparison group was added to the quantitative pre-experimental one-group pretest-posttest design to put the findings in context. The experimental group consisted of fifty students, while the comparison group consisted of fifty-eight. The intervention comprised a singular five hour career planning session. Data were examined via paired sample and independent sample t-tests, with effect sizes computed by Cohen’s d. CDSE scores in the experimental group increased slightly from pretest (M = 119.34) to posttest (M = 122.52); however, the improvement was not statistically significant (p = 0.439) and indicated a small effect size (d = 0.11). No significant differences were seen between groups at the posttest. These results show that a single intensive session is insufficient to significantly increase career decision-making self-efficacy, which advances research on short-term career interventions. The results emphasize the need for continuous, multi-session, hands-on school-based career programs to improve the career readiness of vocational students. Keywords: career decision self-efficacy, career planning, pretest–posttest, school-based intervention, vocational high school